Measurement of the cross-section for Z->e+e- production in pp collisions at sqrts=7TeV - collaboration, L; Aaij, R; Beteta, C; Adametz, A; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; et al. (2012)
A measurement of the cross-section for pp->Z->e+e- is presented using data at sqrts=7TeV corresponding to an integrated luminosity of 0.94 fb^{-1}. The process is measured within the kinematic acceptance pT>20GeV/c and 2<η<4.5 for the daughter electrons and dielectron invariant mass in the range 60--120GeV/c^2. The cross-section is determined to be σ(pp->Z->e+e-)=76.0+-0.8+-2.0+-2.6pb where the first uncertainty is statistical, the second is systematic and the third is the uncertainty in the luminosity. The measurement is performed as a function of Z rapidity and as a function of an angular variable which is closely related to the Z transverse momentum. The results are compared with previous LHCb measurements and with theoretical predictions from QCD.